Exponentially Fitted Diagonally Implicit EDITRK Method for Solving ODEs - Fawzi, Firas A.; Jaleel, Nour W. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
This paper derives the EDITRK4 technique, which is an exponentially fitted diagonally implicit RK method for solving ODEs . This approach is intended to integrate exactly initial value problems (IVPs), their solutions consist of linear combinations of the group functions and for exponentially fitting problems, with being the problem’s major frequency utilized to improve the precision of the method. The modified method EDITRK4 is a new three-stage fourth-order exponentially-fitted diagonally implicit approach for solving IVPs with functions that are exponential as solutions. Different forms of -order ODEs must be derived using the modified system, and when the same issue is reduced to a framework of equations that can be solved using conventional RK approaches, numerical comparisons must be done. The findings show that the novel approach is more efficacious than previously published methods.